Human multidrug resistance protein 8 (MRP8/ABCC11), an apical efflux pump for steroid sulfates, is an axonal protein of the CNS and peripheral nervous system - Bortfeld, Miriam; Rius, Maria; König, Jörg; Herold-Mende, Christel; Keppler, Dietrich (Neuroscience, 2006)
Dehydroepiandrosterone 3-sulfate and other neurosteroids are synthesized in the CNS and peripheral nervous system where they may modulate neuronal excitability by interacting with ligand-gated ion channels. For this modulatory activity, neurosteroids have to be locally released from either neurons or glial cells. We here identify the integral membrane protein ABCC11 (multidrug resistance protein 8) as an ATP-dependent efflux pump for steroid sulfates, including dehydroepiandrosterone 3-sulfate, and localize it to axons of the human CNS and peripheral nervous system. ABCC11 mRNA was detected in human brain by real-time polymerase chain reaction. Antibodies raised against ABCC11 served to detect the protein in brain by immunoblotting and immunofluorescence microscopy. ABCC11 was preferentially found in the white matter of the brain and co-localized with neurofilaments indicating that it is an axonal protein. Additionally, ABCC11 was localized to axons of the peripheral nervous system. For functional studies, ABCC11 was expressed in polarized Madin-Darby canine kidney cells where it was sorted to the apical membrane. This apical sorting is in accordance with the localization of ABCC11 to the axonal membrane of neurons. Inside-out plasma membrane vesicles containing recombinant ABCC11 mediated ATP-dependent transport of dehydroepiandrosterone 3-sulfate with a Km value of 21 μM. This transport function together with the localization of the ABCC11 protein in vicinity to GABAA receptors is consistent with a role of ABCC11 in dehydroepiandrosterone 3-sulfate release from neurons to sites of dehydroepiandrosterone 3-sulfate-mediated receptor modulation. Our findings may provide a basis for the characterization of mutations in the human ABCC11 gene and their linkage with neurological disorders.
Available online 15 December 2005
Gesehen am 18.02.2021